Minutes of the Annual Business Meeting San Antonio, TX January 5, 2024r. - ROUSSEAU, PETER L. (AEA Papers & Proceedings, 2024)
The one hundred thirty-sixth annual meeting of the American Economic Association (AEA) took place in San Antonio, Texas. The meeting covered various topics such as the minutes of the previous annual business meeting, reports from journals and committees, and initiatives for improving the professional climate. It also discussed the results of the annual election, a new dues structure, financial statements, and updates from the Association's journals. The meeting concluded with resolutions expressing appreciation for the editor of AEJ: Macro and the convention manager. Gwyn Loftis, who remained calm and composed throughout the challenges and changes, was recognized for her dedication and contributions with a standing round of applause. Peter L. Rousseau, the secretary, was also honored for his ten years of outstanding service to the Association. The meeting concluded at 7:05 pm.